PENGARUH TINGKAT PENDIDIKAN, PENDAPATAN DAN POLA ASUH ORANG TUA TERHADAP PRESTASI BELAJAR IPS SISWA - Ellen Margaretha (Jurnal Penelitian dan Pendidikan IPS, 2015)
The education level of  parents will have an impact on their children's education, income level of parents as funds that bear the cost of education for smooth teaching and learning in schools. Besides parental guidance had an influence on the social development of children both within the community and school, good parenting will be describing the motivation of children to excel in school. This study is a qualitative research with total 150 students and 108 students in the sample. There are three variables that will be studied in this research are: education level (X1), income level (X2), parental guidance (X3) and student achievement (Y). The collection of data obtained through questionnaires and documentation. Based on the hypothesis test 1 with a value of 2,938 F hitung t> compared with a value of 2,690 Ftabel Ho is rejected proving parental education had a stake of 15,.0%. Hypothesis 2, where the value of F hitung 2920> of Ftabel value of 2,690 hence Ho refused a donation of 16,0%. Hypothesis 3, where the value of  F hitung 2943> of Ftabel value of 2,690 hence Ho refused donations 13,5 %. Hypothesis 4, the constant of 63 393 pales if the teaching methods and the motivation to learn the value 0, then the value of 63 393 achievements. The regression coefficient variable educational level of parents 2081 pales parental education increases one unit, the achievement will be increased by 2,081. Likewise the variable parents' income will increase by 0343. While on parenting parents are 0.043, the achievement will increase by 0043. The effective contribution of parental education, parental income and parenting together to Social Science Study achievement  amounted to 44,5 %. This data indicate that  the influence of students' perception is more dominant and while 55,5 % of other factors